PERBEDAAN PERKEMBANGAN BAHASA DAN KOGNITIF ANAK USIA PRASEKOLAH (5-6 TH) ANTARA YANG MENGIKUTI DENGAN YANG TIDAK MENGIKUTI PAUD DI TK ADITUKA AL ISLAM CANDIPURO - Novita Tri Budi Lestari; Yessy Nur Endah Sary; Muthmainnah Zakiyyah (NHM PRESS, 2023)
Language development is one indicator of the overall development of a child's cognitive abilities associated with success in school. Cognitive development in children is very important to develop at an early age because it can shape the character of children. Language delays can affect personal social life, learning difficulties, and even obstacles to work later. ECCE supports children's growth and development optimally, because the ECCE environment is rich in stimulation. This study used analytical observation method with cross sectional approach. The sample was selected using the total sampling technique. The number of respondents was 47 children consisting of 26 children who attended ECCE and 21 children who did not attend ECCE studied in May 2023. The research instruments are the Denver Development Screening Test II to measure language development and the cognitive development questionnaire sheet to measure cognitive development. This study used a non-parametric statistical test, Chi Square. The results showed that normal category language development in children who attended ECCE (100%) was higher than children who did not attend ECCE (80.9%) with a significant result P value = 0.034. Good cognitive development in children who attended ECCE (100%) was higher than children who did not attend ECCE (80.9%) with a significant result P value = 0.034. This study is expected to be a reference for other researchers, and as information for parents in particular to be more concerned about children's growth and development.